Determinants of Trust in E-Wallet Security: A Study Among Malaysian Undergraduates - Azura Abdullah Effendi; Haslindar Ibrahim; Garima Mathur; Muhammad Faiz Ameen Bin Bhurhanuddeen; Muhammad Arif Bin Azahari; Muhammad Akram Bin Abdul Rahman; Muhammad Hasif Bin Azizan; Daisy Mui Hung Kee (Journal of The Community Development in Asia, 2026)
This study examines the key factors influencing trust in e-wallet security among Malaysian undergraduate students. Using an online survey, data were collected from undergraduates across various universities in Malaysia to identify determinants such as perceived security, privacy protection, user interface quality, trust in service providers, regulatory assurance, and prior user experiences. The findings reveal that students’ trust in e-wallet platforms is strongly shaped by their perceptions of data security, platform transparency, and awareness of cybersecurity practices. Platforms offering clear encryption mechanisms, biometric authentication, and prompt responses to fraud incidents tend to generate higher levels of user trust. Despite the widespread adoption of digital payment systems, concerns related to data breaches and the misuse of personal information remain significant. The study underscores the need for continuous improvements in security features, enhanced user education on digital safety, and transparent policy frameworks to strengthen trust in e-wallet systems. These findings offer valuable insights for policymakers, financial institutions, and application developers seeking to foster a secure, reliable, and inclusive digital payment environment for young users in Malaysia, thereby supporting broader goals of digital inclusion and community developmentDeterminants of Trust in E-Wallet Security: A Study Among Malaysian Undergraduates